The spectacular favela: violence in modern Brazil - Robb Larkins, Erika (California series in public anthropology, 2015)
"This book examines the political economy of violence in the Rio de Janeiro favela of Rocinha. Based on over two years of research and residence in the community, it offers an ethnographic account of how entangled forms of violence become essential forces shaping everyday social relations in the favela. The first part of the book shows how armed actors--drug traffickers and police--use spectacle to perform power. Yet despite the prevalence of physical violence, the favela has itself become a valuable global brand, consumed in disembodied fashion through media and in embodied fashion through tourism. Exploring media and favela tourism, the second part of the book demonstrates how the social relationships that arise from ongoing favela violence have a direct relationship to the market economy"--Provided by publisher